The trauma-sensitive classroom : building resilience with compassionate teaching - Jennings, Patricia A. (New York W.W. Norton & Company, 2019)
"A teacher's guide to recognizing and responding to trauma-exposed students. Chronic stress and trauma can have devastating effects on children's development, making it very difficult for them to function well at school. In this new book the author of Mindfulness for Teachers shares classroom-tested, compassionate teaching practices that support students' healing, build their resilience, and create safe places for them to learn" --
Introduction: why we need compassionate teaching -- Understanding trauma in schools -- Understanding trauma and chronic stress -- When trauma comes to school -- Addressing trauma in schools -- Building supportive relationships -- Creating safe spaces -- Supporting prosocial behavior -- Building resilience with mindful compassion -- Building resilience -- Mindful awareness -- Compassion -- Cultivating compassion in the classroom.
Includes bibliographical references (pages 178-189) and index.
Keywords: Affective education; Emotional intelligence -- Study and teaching; Psychic trauma in children; Stress in children -- Prevention